Social Capital versus Democracy? - Lasierra Esteban, José Manuel (Revista del CLAD Reforma y Democracia, 2020)
This paper develops an empirical analysis that examines the demographic, socioeconomic and ideological profile of individuals associated with nine (9) different types of associations. It is verified that the profile of the associates is different according to the type of association and also different from that of the non-associated. Although the profile of the associates changes according to the type of association, there is a number of variables that appear in almost all types of associations such as interest in politics, income level, occupation, age and male predominance. This leads to confirm the hypothesis that associationism, in any of its types, is a matter of the upper classes that benefit from the benefits provided by associationism in general, which makes them increase their personal and relational capital. The conclusion would be that the associationism probably aggravates social inequality.